Rupture of an unsuspected ectopic pregnancy following a hysterosalpingography—A case report. (2019) - Lim, P.T.; Rohit; Viardot-Foucault, V.
Highlights: HSG should be scheduled during the follicular phase, between Day 5 and Day 12 of a 28 days menstrual cycle and only after menstrual flow has stopped. Patients should practice safe sex during the cycle where HSG is performed. Patients should be informed about the risk of undetected pregnancy that could lead to serious complications once the HSG is done. Women with cycles < 21 or >35 days, with unreliable menstrual history or unusual menstrual flow pattern, should have a pregnancy test before HSG. At present, there is insufficient evidence to recommend universal pre-procedural pregnancy testing. Abstract: Introduction: Hysterosalpingography (HSG) is routinely performed in the mid-follicular phase of a woman's menstrual cycle for cavity and tubal patency assessment as a part of the infertility screening. A pre-procedural pregnancy test is not routinely required unless the patient reports abnormal menstrual bleeding or irregular menstrual pattern. Presentation of case: We present the case of a 29 year-old sub fertile woman who had a HSG performed on day 12 of her menstrual cycle. She developed abdominal pain shortly after and was diagnosed with a ruptured ectopic pregnancy, resulting in a right salpingectomy. The patient was discharged well 3 days later. Discussion: Based on available guidelines and the rare occurrence of such complication, we find insufficient evidence to perform universal pre-procedural pregnancy testing. However, we strongly recommend doing it for abnormal menstrual cycles (cycles shorter than 21 or longer than 35 days, unreliable menstrual history or unusual menstrual flow pattern). Furthermore, HSG should be scheduled during the follicular phase after practicing safe sex within the two weeks preceding the test. Conclusion: While pre-procedural pregnancy test should not be performed for all, a high index of suspicion for early pregnancy should be maintained as undetected ectopic and heterotopic pregnancies could lead to serious complications once the HSG is done.